OPTIMALISASI BREASTFEEDING PADA IBU POST SECTIO CAESARIA DI RSUD PANGERAN JAYA SUMITRA KABUPATEN KOTABARU : Optimization Of Breastfeeding In Post-Sectio Caesaria Mothers At Pangeran Jaya Sumitra Hospital, Kotabaru Regency - Barliyani, Dianti; Dona, Sismeri; Darsono, Putri Vidiasari (LPPM - STIKES Pemkab Jombang, 2024)
Breastfeeding is the activity of giving breast milk (ASI) from the mother's breast to the baby. Special circumstances that hinder breastfeeding, such as mothers who give birth by cesarean section so that mothers stop breastfeeding and post-cesarean pain experienced by mothers which results in mothers not being optimal in breastfeeding their babies. The coverage of exclusive breastfeeding in the Kotabaru area in 2021 is still low (54% of the target of 95%). The total number of mothers giving birth in Kotabaru Regency in 2021 is 9,253 people. The objective is to knowing the optimization of breastfeeding for post sectio caesaria mothers at Pangeran Jaya Sumitra Hospital, Kotabaru Regency. Knowing the optimization of breastfeeding in post sectio caesaria mothers in Pang Hospital. Descriptive research method. The population of all post sectio caesaria was 30 people. The sample uses total sampling. The instrument used observation sheets and questionnaires which were analyzed univariately by Jaya Sumitra, Kotabaru Regency. The results showed that of the 30 respondents, there were 10 people (33.3%) in the category of not optimal Breastfeeding mothers and 20 people (66.7%) in the optimal category of Breastfeeding mothers. Breastfeeding has been carried out optimally for post sectio caesaria mothers.